PENDIDIKAN ISLAM BERWAWASAN MULTIKULTURAL - ansari, ansari (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2019)
Islamic education multicultural brings an insightful approach to instill awareness dialogis living together in diversity and differences, education is built on the spirit of equality and partnership kesederajatan, mutual trust, mutual understanding and appreciate the similarities, differences and uniqueness, as well as interdepedensi. This is an innovation and an integral and comprehensive reforms in the educational payload of religions that are free of prejudice, racism, bias and stereotypes. Islamic education multicultural gave insightful recognition of plurality, a learning tool for cross-border encounters, and transforms indoctrination toward dialogue. This will be determined by the quality and the role of the teacher in the learning process of Islamic education in schools. However, the burden is not only on the shoulders of workers education but is also the responsibility of the family, society and the State, autonomous and independent.